2015
DOI: 10.1016/j.biotechadv.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

BBB-targeting, protein-based nanomedicines for drug and nucleic acid delivery to the CNS

Abstract: 24The increasing incidence of diseases affecting the central nervous system 25 (CNS) demands the urgent development of efficient drugs. While many of 26 these medicines are already available, the Blood Brain Barrier and to a lesser 27 extent, the Blood Spinal Cord Barrier pose physical and biological limitations 28 to their diffusion to reach target tissues. Therefore, efforts are needed not only 29 to address drug development but specially to design suitable vehicles for 30 delivery into the CNS through syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 123 publications
(10 reference statements)
0
32
0
Order By: Relevance
“…To address this challenge, variety of macromolecule delivery approaches or reagents have been developed. Perhaps cell-penetrating peptide (CPP)-based delivery system is the most common and safe method for the introduction of exogenous macromolecule to transiently manipulate cell behavior without possibility of permanent genomic changes [3]. …”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, variety of macromolecule delivery approaches or reagents have been developed. Perhaps cell-penetrating peptide (CPP)-based delivery system is the most common and safe method for the introduction of exogenous macromolecule to transiently manipulate cell behavior without possibility of permanent genomic changes [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Against this background of hindrance to brain tumor delivery, nanomedicine may enhance the distribution of poorly brain-distributed anticancer agents across the brain endothelium, since nanocarriers may well serve to target brain tumors through passive and active targeting or even through external physical stimuli [53]. Passive targeting occurs with the diffusion of nanomedicines through the interendothelial gaps of the highly vascularized leaky BBTB in the case of high-grade brain tumors, a phenomenon known as the enhanced retention and permeation (EPR) effect [54].…”
Section: Systemic Delivery Of Nanomedicinesmentioning
confidence: 99%
“…Although great advances have been made in recent years, the field of BBB drug targeting is in its infancy and only very few current treatments make use of BBB drug delivery techniques. 123,124 Because many of the discussed morphogens -such as Wnt/ b-catenin, TGF-b, and the BMPs -are essential for a wide range of biological processes and the angiopoietins are essential for vessel development and integrity throughout the body, we propose that of these morphogens the semaphorins are the best option for treating BBB breakdown in CNS disorders. Recent studies have shown promising results regarding the use of anti-sema4D therapies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%